Challenges of Large-Scale Agile Transformation A Case Study at a Manufacturing Firm - Linnakallio, Ida (My University, 2025)
This master’s thesis explores the challenges associated with large-scale agile transformation within a manufacturing firm. Adopting a qualitative single-case study approach, the research draws on data from semi-structured interviews, internal documents, and field notes, focusing on a single platform within the organization to provide an in-depth understanding of the transformation process. Several key challenges were identified across multiple dimensions, which impacted the overall success and effectiveness of the agile transformation. These challenges, though varied stem from factors related to process, technology, organizational structure, and people. The discussion emphasizes the most significant challenges within each dimension, exploring their impact on the agile transformation and highlighting the complex nature of implementing agile at scale in a non-IT-centric environment. The thesis presents a set of practical recommendations to address these challenges, including the need to improve communication and collaboration across teams, engage stakeholders more effectively, ensure strong leadership involvement, and promote organizational alignment throughout the transformation process. Additionally, the study highlights the importance of cultivating an agile mindset at all levels of the organization, addressing both cultural and psychological barriers to change. The research concludes that successful agile adoption goes beyond changing processes—it requires a fundamental shift in organizational culture and alignment at all levels, emphasizing the importance of leadership, collaboration, and continuous learning. This study contributes to the body of knowledge on agile adoption in manufacturing and other non-IT-centric environments, offering insights into the unique challenges faced by organizations in these contexts. The findings also underscore the necessity of adaptive governance structures, integration strategies, and tailored approaches to agile transformation. The thesis provides managerial implications that can guide organizations through the complexities of agile adoption, focusing on the key aspects of leadership, engagement, and cultural transformation necessary for sustainable success.
Keywords: Agile transformation; Large-scale Agile; Challenges; Process; Technology; Structure; People